Systematic study of ant diversity in tropical dry forests (Zoological Records and Reviews, 2022)
Tropical dry forests are among the most threatened and least studied terrestrial ecosystems globally, supporting highlevels of endemic biodiversity despite their characteristically harsh seasonal climate. Ants (Hymenoptera: Formicidae)are dominant components of tropical dry forest soil and litter communities, performing critical ecosystem functionsincluding seed dispersal, soil aeration, and prey regulation. This study presents a systematic survey of ant diversityacross tropical dry forest sites in the Deccan Plateau of India (Telangana and Karnataka), the Caatinga of northeasternBrazil, and the seasonally dry forests of Oaxaca, Mexico, using standardised pitfall trap, winkler litter extraction, andbaiting protocols at 54 sites surveyed during both wet and dry seasons. A total of 284 ant species belonging to 58 generaand 11 subfamilies were documented across all sites. Species richness was highest in the Brazilian Caatinga sites (mean84.2 species per site) and lowest in the Indian Deccan sites (mean 48.6 species per site), consistent with the latitudinaldiversity gradient. Myrmicinae was the dominant subfamily at all sites (42.6% of species), followed by Formicinae(18.3%) and Ponerinae (14.1%). Functional guild composition differed significantly among regions, with generalisedMyrmicini dominant in Indian sites and specialist army ant foragers more prominent in Neotropical sites. Habitatdisturbance gradient analysis reveals that selective logging reduces ant species richness by 28.4% and dramaticallyalters functional guild composition. An updated key to Indian tropical dry forest ant genera is provided.